Lateral dominance of stretch-shortening cycle performance in unilateral and bilateral athletes - Miyaguchi, K.; Demura, S. (The Journal of Sports Medicine and Physical Fitness, 2008)
Aim. Few studies have been conducted on the lateral dominance of stretch-shortening cycle (SSC) performance. This study aimed to make an index for evaluation of the ability to use SSC for powerful elbow flexion and to examine the lateral dominance of SSC performance in unilateral and bilateral athletes. Methods. Thirty-three male athletes (19.9±1 years) participated in this study. Each subject pulled a submaximal load (25% of maximum voluntary contraction [MVC]) in a single burst via elbow flexion of the dominant and non-dominant upper limb from the following two preliminary conditions: a static relaxed muscle state (SR condition) and using a counter-movement (SSC condition). Muscle power was measured accurately with a power instrument containing a rotary encoder, and the SSC index was calculated in order to evaluate the ability to use SSC. Results. For the SSC index, the non-dominant upper limb showed higher values than the dominant upper limb. The unilateral athletes showed high values of power output when using only SSC in the dominant upper limb compared with bilateral athletes. The correlation in the SSC index between dominant and non-dominant limbs was found to be low. Conclusion. The non-dominant limb is superior to the dominant limb in the ability to use SSC in the upper limbs and there is the possibility of left side dominance. Unilateral athletes were superior to bilateral athletes in their ability to use SSC with their dominant limb, but a transfer of learning to the non-dominant limbs was not apparent.